Curbing bureaucratic limitations through continuous learning in local government in South Africa - Shava, Elvin; Muringa, Tigere Paidamoyo (Frontiers in Political Science, 2024)
The local government in South Africa faces a dire scenario as it relentlessly fails to execute its legally mandated responsibilities of rendering essential goods and services. Despite various legal frameworks (The Municipal Systems Act 2000; The Municipal Finance Management Act (MFMA) 2003) and government interventions (The Batho Pele Principles 1997) to address the bureaucratic limitations, local government continues to transgress, resulting in many local municipalities receiving adverse audit outcomes from the Auditor General every year. Prior research on local government in South Africa has not extensively investigated the effects of continuous learning on mitigating bureaucratic limitations and promoting efficiency and effectiveness in municipal service delivery. This paper examines the role of learning organizations, guided by Pete Senge’s Model of Learning Organizations, in mitigating bureaucratic limitations within South African local governments. Using a qualitative case study approach, the research explores how continuous learning platforms can contribute to overcoming these limitations and enhancing municipal service delivery. A purposive sampling technique was employed to select 50 participants from 10 municipalities across six South African provinces, ensuring representation from various managerial levels within local governments. The study’s key findings reveal that if properly implemented, continuous learning frameworks can address critical issues such as administrative inefficiency and resistance to innovation, which are deeply embedded in bureaucratic structures. The findings also highlight that change management strategies, grounded in collaborative learning and shared vision, are essential for fostering an environment conducive to organizational transformation. However, the study identified significant challenges, including political interference, staff turnover, and cultural resistance, which limit the effectiveness of learning organizations. Based on these findings, the study recommends targeted interventions that promote leadership development, skills enhancement, and policy reform to create a sustainable culture of continuous learning in local government.